TEACHING LEGAL ENGLISH TO LAW SCHOOL STUDENTS THROUGH VOCABULARY PRACTICE TASKS - CRISTINA PIELMUŞ (Studia Universitatis Babes-Bolyai, 2018)
ABSTRACT. The paper aims to demonstrate that students can learn and reinforce Legal English vocabulary through practical tasks developed based on authentic materials. The arguments to support such a demonstration consist in showcasing a variety of examples of practical vocabulary tasks that we have developed and used in class with our students. Yet, before shifting to the practical facets of teaching Legal English to law school students, the article debuts with a clarification of some concepts related to English language teaching, as well as with language teaching approaches, which is further followed by a brief analysis of the teaching resources available for Legal English and their advantages. As previously mentioned, the final section of the paper is devoted to the extensive exemplification of the possibilities a language instructor can use in a Legal English class based on the practical tasks he/she may design and develop starting from authentic materials. The teaching practice, however, has revealed that, though students can as well acquire legal English terminology while being engaged in and as a result of vocabulary‐based practical tasks, the degree of effectiveness of their learning of English legal concepts is higher if learning is contextualized.